STRATEGI PEMBELAJARAN PARTISIPATIF DALAM PELATIHAN VOKASIONAL MENGEMUDI DI LPK CEMERLANG TEKNIK - Juniardi Febryansyah; Ari Putra; Dwi Ismawati (Comm-Edu (Community Education Journal), 2026)
This study examines the implementation of participatory learning strategies in vocational driving training within the Indonesian nonformal education sector, specifically at LPK Cemerlang Teknik in Bengkulu City. This research has explored application in technical skills training such as driving instruction. Using a qualitative descriptive approach, this study collected data through in-depth interviews with the institution head, two driving instructors, and trainees, complemented by participatory observation and document analysis. Data triangulation ensured validity and reliability. Findings reveal that participatory learning strategies are implemented through: (1) active trainee involvement in planning training schedules and materials, (2) student-centered instructional delivery emphasizing demonstration, simulation, and hands-on practice, and (3) reflective evaluation processes engaging trainees in self-assessment. Instructors function as facilitators providing guidance, immediate feedback, and adaptive teaching methods aligned with individual abilities and needs. Supporting factors include instructor competence and experience, adequate facilities and infrastructure, and high trainee motivation. Barriers include diverse trainee backgrounds and abilities, and unpredictable weather conditions. This research addresses a significant gap by examining participatory strategies from multi-stakeholder perspectives in a context-specific Indonesian vocational training setting.